Comparative Analysis of Cryptocurrencies Versus Shares - Ovidiu-Constantin BUNGET; Georgiana-Iulia TRIFA (CECCAR Business Review, 2023)

(untitled)
As the limit between reality and the digital field seems to blur more and more, and this fusion has an impact on several fields of study, such as accounting and audit, the similarity between cryptocurrencies and the shares of companies has to be analysed, as investment items. In the absence of comparisons between the cryptocurrency market and the capital market, investors cannot apply the proper accounting treatment for the activity in which they are involved. Consequently, the aim of this article is setting the existing characteristics and correlations between the cryptocurrency market and the securities market. Besides, the authors consider that this article may contribute to the accounting research, providing useful information to investors and regulatory authorities in accounting. Cryptocurrencies and the prices of shares are somehow correlated after considering the volatility of cryptocurrency. Many of the factors affecting the prices of shares also have an impact on the prices of cryptocurrencies. Investors and traders treat cryptocurrency in the same way in which they treat the shares, so that prices tend to have the same trend. We should be cautious when we invest in cryptocurrencies, as they are still new – the market explores its role as an asset. At the same time, the analysis and presentation of certain statistical data was pursued, like the number of companies listed at the largest stock exchange operators in the world, the stock exchange capitalization, the number of cryptocurrencies at world level, the market capitalization of cryptocurrencies, resulting in a similarity between the two studied elements.